Mourning in the death mother complex - Pompa Guajardo, Edith Gerardina; Campero Anchondo, María Andrea; García Cantú, Walter Daniel (Universidade Federal do Rio de Janeiro, Instituto de Psicologia, 2019)
We review the concept of mourning, first as conceived byFreud and Klein, and how it relates with the contemporary “clinic of the void” as described by André Green. The clinic of the void is partof a series of modern manifestation of psychic malaise called “newsymptoms”. To illustrate, we present the case of Roxana, a Mexican woman whose psyche reflected the dynamic of the dead mother complex. Through an analysis of her interpersonal relationships andpast experiences, and comparing with psychoanalytic literature, we conclude that the dead mother complex might become a common condition in our society.